Amino acid modified gadofullerene protects against insulin resistance induced by oxidative stress in 3T3-L1 adipocytes. Issue 33 (17th July 2020) - Yu, Tong; Jia, Wang; Zhen, Mingming; Zhou, Yue; Li, Jie; Wang, Chunru
Abstract : GF-Ala afforded a significant protection against insulin resistance induced by oxidative stress in 3T3-L1 adipocytes. It could reverse the increase of JNK activation and decreases of insulin-stimulated PI3K, Akt, p70S6K activation and GLUT4 translocation. Abstract : Reactive oxygen species (ROS) have been shown to be involved in the development of insulin resistance; thus, antioxidant therapy is a promising strategy in the treatment of insulin resistance related diseases. In this study, we synthesized a high-efficiency ROS scavenger, an amino acid derivative of Gd@C82 (GF-Ala), and evaluated its effects on ROS-mediated insulin resistance in 3T3-L1 adipocytes. The exposure of adipocytes to H2 O2 (generated by glucose oxidase) resulted in an elevated level of ROS, a reduced content of GSH and an increase in JNK activation, concomitantly with a decrease in insulin-stimulated PI3K, Akt and p70S6K activation and cellular glucose uptake. The pre-treatment of cells with GF-Ala suppressed H2 O2 -induced abnormalities in the cellular redox state and insulin signalling pathway and attenuated insulin resistance in a dose-dependent manner. Altogether, gadofullerene has potential therapeutic prospects in the prevention and treatment of insulin resistance related diseases.